Strategi Konseling Lintas Budaya untuk Mengatasi Hambatan Komunikasi Interpersonal Siswa Akibat Perbedaan Budaya - Oza Salsa; Fadhilla Yusri (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to examine how the application of cross-cultural counseling improves the social adjustment of migrant students from West Java in the Minangkabau school cultural environment. The study uses a qualitative approach with interview and observation methods on the research subject, a student with the initials R.D.A, 18 years old, studying at SMA N 1 X Koto. Data were collected through in-depth interviews and observations to identify patterns of communication barriers and the adjustment process experienced by the subject. The intervention applied used a cross-cultural counseling approach that considers the differences in culture, language, values, customs, and habits of the counselee. The results show that the problems experienced by R.D.A are closely related to differences in language, accent, communication style, and ways of expressing emotions that affect the counselee’s ability to adapt to the social and school environment. This condition leads to low self-confidence, difficulty in social interaction, and barriers in communicating with the surrounding environment. Through the cross-cultural counseling approach, the counseling process helps R.D.A understand that cultural differences are not a weakness but part of self-identity that should be respected, as well as developing communication skills, self-adjustment, and self-confidence in the new social environment. The findings affirm that the application of cross-cultural counseling based on empathy, tolerance, openness, and cultural awareness effectively facilitates the adjustment of migrant students in a culturally diverse school environment without sacrificing their original cultural identity.